A carreira de profissionais de Ti em sistema home-office - Silva, Regiani Salvático Pereira da (2017)
Organizations are seeking different practices to continue competing in the globalized world. Therefore, despite the challenges that work at home presents, more and more companies are adopting this format, mainly based on the advantages that can be obtained for both the employee and the employer. The home office practice requires that the worker be more independent and able to do their self-management. This idea is also present in the contemporary concept of careers, in which the individual himself is responsible for carrying out and planning his career, seeking professional and personal fulfillment. Based on this, the present study aims to investigate the career and workers in the information technology area in São Paulo who work in home office system. For this, a theoretical survey of references was made on technology and the world of work, flexible work and home office, career theories and career anchors. The research was qualitative with a multiple case study of three companies in the information technology sector. Twenty-six professionals, including managers and human resources professionals, were interviewed. The questionnaire was divided into four parts: socio-professional information, home office practice questions, career questions, and lastly the career anchors questionnaire. The analyzes were carried out in two stages: descriptive statistics in which the data are presented in graphs and tables and by the content analysis for the questions in the form of a comment. As a result one can obtain that the career anchor with the highest incidence among the respondents was that of lifestyle, marked by the desire for autonomy and flexibility. It was also possible to find out that most people opted to perform remote work as a career option and that most workers understand that they have the same career growth opportunity as the full-time office workers